PERAN MODAL SOSIAL DALAM KONSISTENSI DAN KEBERLANGSUNGAN INDUSTRI TEKSTIL RAMAH LINGKUNGAN CV. TARUM BALI - Indrayatna, I Gede; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study examines the role of social capital in the consistency and sustainability of the environmentally friendly textile industry in CV. Tarum Bali. The type of research used is descriptive-explanative qualitative research. The theory used is that the author uses Robert D Putnam's thoughts on social capital. According to Putnam, social capital is a part of social life such as networks, norms and beliefs that encourage participation to act together more effectively to achieve common goals. Tarum Bali is able to explore well the role of social capital with the linkage of their business, realizing that the network formed or formed by Tarum Bali supports their production process. Keywords: The role of social capital, textile industry, CV. Tarum Bali